How Good at Neurology are you? – Answers. Issue 1 (1st February 2004) - Goldsmith, Paul; Lennox, Graham; Ray, Julian
Abstract : 1. Paget's disease. He has cataracts and prostatic outflow obstruction, common pathologies in older people. However, his deafness and back pain are due to Paget's disease. The Xray shows a coarseness of the L2-4 vertebral bodies and blurring of the cortico-medullary junction. The bodies are also quite flat and there is thickening of the right border of L3. Further Reading Hadjipavlou AG, Gaitanis LN, Katonis PG, Lander P (2001) Paget's disease of the spine and its management. European Spine Journal, 10, 370–84. 2. Low CSF volume headache. This pattern of diffuse meningeal enhancement following gadolinium injection is typical of low CSF volume headache. 90% of such cases can be picked up by this means. Other causes of meningeal enhancement, such as malignant infiltration or sarcoidosis, are more likely to give a nodular, rather than smooth, pattern. Further Reading Goads by PJ, Boes C & Sudlow CLM (2002) Low CSF